ANALISIS KARAKTERISTIK DAN KEBUTUHAN RUANG PARKIR PADA PUSAT PERBELANJAAN DI KABUPATEN BADUNG - Suthanaya, Putu Alit (Jurnal Ilmiah Teknik Sipil; Vol. 14, No. 1 Januari 2010)
The increase of activities particularly shopping centers in Badung Regency, requires sufficient supply of parking facility. However, so far there is no study on parking characteristics and quantification of standard parking spaces demand. The objectives of this study are to evaluate parking characteristics on shopping centers in Badung Regency and to analyse standard of parking spaces demand. Data required are primary data which is obtained from survey on site to obtain parking characteristics and secondary data is obtained from the shopping centers management which is used to analyse standard parking space demand. Results of the study indicate that for light vehicle, parking index based on average parking accumulation is 0,72, while for motor cycles it is 3,09. Relationship model between average parking accumulation for light vehicle on working days is y = 0,0016x + 9,289 (R2 = 0,8786) and for motor cycle is y = 0,0032x + 123,69 (R2 = 0,5776). Average parking accumulation required for the maximum floor area of building of 75.648 m2 is 178 vehicles/hour with 194 spaces and 434 motor cycles/hour with 1.209 spaces. For the minimum floor area of building of 5.000 m2, average parking accumulation required is 19 vehicles/hour with 21 spaces and 141 motor cycles/hour with 393 spaces.
Keywords: Parking characteristics, parking space demand, shopping centers.